2017
DOI: 10.3899/jrheum.161436
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Prognosis of 121 Patients with Eosinophilic Granulomatosis with Polyangiitis in Japan

Abstract: Patients with myocardial or GI tract involvement had frequent relapses, but these conditions were not reflected in increased mortality. Treatment with immunosuppressants or IVIG in addition to corticosteroids might have improved the prognosis in Japanese patients with EGPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 36 publications
3
45
1
1
Order By: Relevance
“…All six known patients with familial EGPA (Table) were negative for MPO-ANCA, and the two patients reported here were the only ones without house dust mite (HDM) sensitization. There was no marked difference in the types or ratios of organ involvement between cases of familial EGPA and the previously reported non-familial EGPA cases (7,(12)(13)(14).…”
Section: Discussioncontrasting
confidence: 57%
“…All six known patients with familial EGPA (Table) were negative for MPO-ANCA, and the two patients reported here were the only ones without house dust mite (HDM) sensitization. There was no marked difference in the types or ratios of organ involvement between cases of familial EGPA and the previously reported non-familial EGPA cases (7,(12)(13)(14).…”
Section: Discussioncontrasting
confidence: 57%
“…53 It is reported that 22.7% to 42.6% of patients with EGPA are positive for MPO-ANCAs or ANCAs. 2,[54][55][56][57][58][59][60] The prevalence of ANCAs in EGPA patients was less than that in microscopic polyangiitis or granulomatosis polyangiitis, such as ANCA-associated vasculitis. In the present study, there was no difference in serum IL-33 concentra- 27 In the present study, we had detected more CD4 + T cells producing IL-25 in peripheral blood in patients with EGPA at relapse than in those at remission or in patients with BA, although the difference was very small.…”
Section: Discussionmentioning
confidence: 95%
“…Since the publication of the American College of Rheumatology criteria in 1994, better diagnosis methods 37 55 These data suggest that the long-term prognosis for EGPA is poor. Indeed, some patients with EGPA experience frequent relapse (defined as patients who have relapsed at least once in the two years after a period of remission 53 ), and some patients are unable to maintain an extended period of remission.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyopathy and older age at diagnosis were independent risk factors for death and lower eosinophil count at diagnosis as predictive of relapse in multivariate analyses [56]. Myocardial and gastrointestinal tract involvement are indicators of frequent relapses in a series of 121 Japanese patients with EGPA [59].…”
Section: Prognosis or Clinical Coursementioning
confidence: 99%